The National High School of Nurses of Colombia: relations with inter-American organisms - Ana Luisa Velandia Mora (Universidad de Alicante, 2012)
This writing is a contribution to the project: "Formation of personnel of infirmary in the National University of Colombia", that carries out the Group of Investigation in Nursing History in the same University. This work has as objective present history the National Nursing High School of the National University of Colombia - ENSE, from its creation in 1943 to its transformation in Faculty of Infirmary, in 1958. The National Nursing High School is an emblematic institution in the Colombian infirmary and is part of a representative time of the direction of the health services towards an approach hygienist, promoted in all the continent by inter-American organisms. This phenomenon happens in a time in a context characterized by great legal development in nursing, as much by prescribed laws of the profession, like by prescribed decrees of the nursing schools, and especially by the legal prerogatives that granted to the National Nursing High School. On the other hand, this school can be considered as one of the pillars of the implantation in Colombia of the American influence that arrived from the United States and Canada, countries that had received "the nightinguiliana" influence, of English nurses, in second half of Century XIX.